SOX12 Promotes Stem Cell-Like Phenotypes and Osteosarcoma Tumor Growth by Upregulating JAGGED1 - Weifei Zhang; Fei Yu; Jian Weng; Yien Zheng; Jianjing Lin; Tiantian Qi; Yihao Wei; Deli Wang; Hui Zeng (Hindawi Limited, 2021)
SOX12 plays a role in promoting the growth of some tumors; however, its role in osteosarcoma remains unclear. From gene expression omnibus (GEO) and tumor alterations relevant for genomics-driven therapy (TARGET) databases, Kaplan-Meier analyses were conducted to establish relationships between SOX12 expression and osteosarcoma survival and recurrence in osteosarcoma patients. We also performed in vitro and in vivo assays to determine SOX12 function in osteosarcoma etiology. SOX12 expression was increased in osteosarcoma; high SOX12 expression levels were related to a poor prognosis and a high disease recurrence in patients. Moreover, SOX12 expression in osteosarcoma cell lines was increased, similar to osteosarcoma cancer stem cells. We also observed that SOX12 knockdown inhibited the spheroidization and expression of stemness markers in osteosarcoma cells and tumor formation in nude mice. In addition, SOX12 knockdown inhibited JAGGED1 and HES1 expression. Similarly, JAGGED1 knockdown also inhibited the formation of osteosarcoma cancer stem cells into pellets and reduced the expression of stemness markers and tumor formation capabilities in nude mice. Finally, during SOX12 knockdown, JAGGED1 overexpression rescued osteosarcoma cells from spheroidizing. SOX12 promotes stem cell-like phenotypes and osteosarcoma tumor growth by upregulating JAGGED1.